PEMBANGUNAN SISTEM INFORMASI MANAJEMEN SEKOLAH BERBASIS WEB GUNA MENINGKATKAN EFEKTIFITAS PENGELOLAAN AKADEMIK DAN NON AKADEMIK PADA SMPN 1 PERCUT SEI TUAN (UIN Sumatera Utara Medan, 2022)
Many schools have implemented information systems that can make it easier for users to access the required data. However, SMPN 1 Percut Sei Tuan still uses manual methods to manage academic and non-academic data which causes the process of delivering academic and non-academic information there to not run optimally and lack of academic and non-academic communication between teachers and students. Based on this background, a school management information system was built as an effort to increase the effectiveness of academic and non-academic management at SMPN 1 Percut Sei Tuan.